Protocol‐based nurse coordinator management of ambulatory tacrolimus dosing in de novo renal transplant recipients—A single‐center experience with a large African American population. Issue 10 (12th September 2019) - Elmaasarani, Zana; Mardis, Caitlin; Gylten, Logan; Taber, David J.; Fleming, James; Patel, Neha; Baliga, Prabhakar; Rao, Vinaya; Rohan, Vinayak; DuBay, Derek; Pilch, Nicole A.
Abstract: Introduction: Transplant nurse (RN) coordinators review tacrolimus levels frequently and would be capable of making dose adjustments autonomously if not limited by their license. Collaborative practice agreements could be an answer; thus, the aim of this evaluation was to determine if an RN‐driven protocol could be used safely and effectively to manage tacrolimus in ambulatory kidney transplant (KTX) recipients. Methods: This was a retrospective review of all solitary adult KTX recipients between August 1, 2016, and July 29, 2017. The primary objective was to evaluate protocol adherence and frequency of use, and secondary objectives were to evaluate the utility of the protocol both overall and based on ethnicity. Results: A total of 173 patients were included in the evaluation (59% African American [AA], 41% non‐African American [non‐AA). RN coordinators followed the protocol for 75% of tacrolimus adjustments; however, they only responded to 27% of the overall levels. There was no difference in 180‐day tacrolimus‐associated readmission (15% AA vs 5% non‐AA, P = .06), biopsy‐proven acute rejection (4% AA vs 7% non‐AA, P = .363), or hyperkalemia (34% AA vs 32% non‐AA, P = .87) between groups. Conclusions: Transplant nurse coordinators are capable of accurately following a protocol for tacrolimus dosage adjustment in a large, racially diverse kidney transplant center.